PERANCANGAN ALAT PEMBUAT PAVING BLOCK DARI LIMBAH SAMPAH PLASTIK DENGAN MENGGUNAKAN PENDEKATAN ERGONOMI DAN METODE KANSEI ENGINEERING - Adiasa, Iksan; Aldrin; Fauzi, Rival; Lestari, Fitri (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2023)
Plastic is a well-known product that is often found everywhere. The existence of plastic in Indonesia is very important for Indonesian people. However, increasing plastic consumption causes an increase in plastic waste produced. The resulting result is that the environment is dirty and of course unhealthy. One way to reduce plastic waste is to process it into paving blocks with high selling value. However, the current tools are not ergonomic and risk causing workers to experience work-related illnesses. Therefore, it is necessary to design tools that are more ergonomic. This study aims to design a tool for making plastic waste paving blocks using an ergonomic and Kansei Engineering approach. The ergonomics approach aims to obtain the dimensions of the tool that will be designed to suit the dimensions of the human body as the user. Kansei Engineering aims to get the wishes of potential tool users for the plastic waste paving block making tools they will use. The results obtained by the user's wishes are easy to use, easy to move, colorful, bright in color, striking, thick and the design is obtained according to the user's body dimensions. Offers of tools designed to increase the productivity of making paving blocks from plastic waste and user comfort in using them.